Flexible Approaches Based on Multistate Models and Microsimulation to Perform Real-World Cost-Effectiveness Analyses: An Application to Proprotein Convertase Subtilisin-Kexin Type 9 Inhibitors - Gregorio, Caterina; Rea, Federico; Ieva, Francesca; Scagnetto, Arjuna; Indennidate, Carla; Cappelletto, Chiara; Di Lenarda, Andrea; Barbati, Giulia (Value in health, 2024)
This study aims to show the application of flexible statistical methods in real-world cost-effectiveness analyses applied in the cardiovascular field, focusing specifically on the use of proprotein convertase subtilisin-kexin type 9 inhibitors for hyperlipidemia. The proposed method allowed us to use an electronic health database to emulate a target trial for cost-effectiveness analysis using multistate modeling and microsimulation. We formally established the study design and provided precise definitions of the causal measures of interest while also outlining the assumptions necessary for accurately estimating these measures using the available data. Additionally, we thoroughly considered goodness-of-fit assessments and sensitivity analyses of the decision model, which are crucial to capture the complexity of individuals’ healthcare pathway and to enhance the validity of this type of health economic models. In the disease model, the Markov assumption was found to be inadequate, and a “time-reset” timescale was implemented together with the use of a time-dependent variable to incorporate past hospitalization history. Furthermore, the microsimulation decision model demonstrated a satisfying goodness of fit, as evidenced by the consistent results obtained in the short-term horizon compared with a nonmodel-based approach. Notably, proprotein convertase subtilisin-kexin type 9 inhibitors revealed their favorable cost-effectiveness only in the long-term follow-up, with a minimum willingness to pay of 39 000 Euro/life years gained. The approach demonstrated its significant utility in several ways. Unlike nonmodel-based or alternative model-based methods, it enabled to (1) investigate long-term cost-effectiveness comprehensively, (2) use an appropriate disease model that aligns with the specific problem under study, and (3) conduct subgroup-specific cost-effectiveness analyses to gain more targeted insights. •Cost-effectiveness analysis utilizing electronic health records databases can offer valuable real-world evidence for drugs recently approved. However, the statistical aspects of economic-health evaluations in chronic illnesses using decision models are often overlooked.•We proposed the application of a flexible multistate decision model based on microsimulation to replicate a target trial using observational data, enabling the study of proprotein convertase subtilisin-kexin type 9 inhibitors cost-effectiveness. Notably, these methods overcome the limitations of standard Markov decision models by considering the dependence of individuals’ healthcare paths on their past.•This study provides novel insights into the real-world cost-effectiveness of proprotein convertase subtilisin-kexin type 9 inhibitors in hyperlipidemia. Furthermore, the statistical approach used here could also be useful for other diseases, treatments, or healthcare systems.